SUPER-TWISTING SLIDING MODE CONTROL STRATEGY FOR DYNAMIC VOLTAGE RESTORER TO IMPROVE POWER QUALITY IN POWER DISTRIBUTION SYSTEM - Kanwal, S.; Hanif, A. (The Nucleus, 2013)
The paper deals with application of super-twisting sliding mode control in Dynamic Voltage Restorer (DVR) to tackle various Power Quality (PQ) issues. The various features of super-twisting sliding mode, which include selection of sliding surface, stability of system, existence of sliding mode and reaching conditions to bring system states on sliding surface, are discussed for mitigation of voltage sag/swell and phase jumps applications. Pulse width modulation (PWM) based second order super-twisting sliding mode control is used to operate voltage source converter (VSC) in voltage control mode for mitigation of voltage sag, voltage swell and phase jumps to regulate power flow to load. The proposed controller design is simulated for single phase DVR. It exhibits robustness to system parameters and load variations. The load voltage Total Harmonic Distortion (THD) is calculated to evaluate the voltage quality. MATLABÂ®/SimulinkÂ® SimPowerSystem tool box is used to check the performance of proposed control strategy. Simulation results show that response time and chattering effect can be minimized with use of super-twisting sliding mode control while keeping the main properties of standard sliding mode control (SMC). The proposed control scheme can compensate voltage sags, voltage swells and phase jumps within 2ms which is reasonably lower than ITIC curve and SEMI-F-47 standard for sensitive loads that suggest a tolerable time limit of 20ms.